Communication Strategies Employed by the Fourth Semester Students of English Department of State University of Makassar - Nasrullah Nasrullah (Jurnal Ad'ministrare, 2017)
The research aims at identifying the types and investigating the reasons of communication strategies employed through English. The research used a qualitative method in nature. The subjects were twenty five students of English Department of State University of Makassar who passed Speaking Three classes. The researcher used Littlewood’s taxonomy of communication strategies in identifying the data and Miles and Huberman interactive model of analysis as the techniques of data analysis. The interview and the observation were carried out simultaneously to elicit and to identify the types of communication strategies employed. The research reveals that there are eight strategies employed in which seeking help strategy was most used in dialogue. It was proved that when the students faced difficulty to express the meaning, they asked for help from the interviewer. The researcher found some reasons of communication strategies, namely making communication running well, catching the message easily, making the speaker more creative, and avoiding being afraid of making wrong words. The thesis argues that, on the basis of the findings, further research into the use of communication strategies in classroom context could make a significant contribution to teacher education.